2022
DOI: 10.1007/s10055-022-00679-7
|View full text |Cite
|
Sign up to set email alerts
|

Training in virtual reality enables learning of a complex sports movement

Abstract: Despite the increased use in sports, it is still unclear to what extent VR training tools can be applied for motor learning of complex movements. Previous VR studies primarily relate to realize performances rather than learning motor skills. Therefore, the current study compared VR with video training realizing the acquisition of karate technique, the Soto Uke moving forward in Zenkutsu Dachi, without being accompanied by a trainer or partner. Further analyses showed whether a less lavished forearm compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…We can say that the practitioners who provide training increase their performance by increasing their motivation during the work. When the literature is examined, we can say that virtual reality contains motivating elements that affect technical skills (Oagaz et al, 2021;Pastel et al, 2022;Romeas et al, 2022;Thatcher et al, 2020;Zhao & Guo, 2022). Nambi et al, (2021) found that balancing training with virtual reality technology had a neurological effect on individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can say that the practitioners who provide training increase their performance by increasing their motivation during the work. When the literature is examined, we can say that virtual reality contains motivating elements that affect technical skills (Oagaz et al, 2021;Pastel et al, 2022;Romeas et al, 2022;Thatcher et al, 2020;Zhao & Guo, 2022). Nambi et al, (2021) found that balancing training with virtual reality technology had a neurological effect on individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Nambi et al, (2021) found that balancing training with virtual reality technology had a neurological effect on individuals. Pastel et al, (2022) found that VR technology was effective in learning these movements in the training they performed using VR technology in learning complex sports movements. DiCesare et al, (2020) stated that VR can be a promising element for transferring sportive skills.…”
Section: Discussionmentioning
confidence: 99%
“…While this technology is becoming popular for entertainment purposes, it is also a vital educational tool used in many fields, including (but not limited to) training in the military, 8 medical applications, 9 and sports. 10 In traditional classroom settings, VR methods have been used for many topics from writing 11 to physics 12 to engineering. 13 VR methods help students interact with course content in an embodied, experiential manner.…”
Section: Virtual Reality In Educationmentioning
confidence: 99%
“…Beyond just allowing users to perceive a space, VR also allows users to interact with virtual objects in the environment. While this technology is becoming popular for entertainment purposes, it is also a vital educational tool used in many fields, including (but not limited to) training in the military, medical applications, and sports . In traditional classroom settings, VR methods have been used for many topics from writing to physics to engineering .…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using virtual reality technology could help student-athletes to have a better understand about the exercises or movements that will be learned in sports [38,39]. Even though, virtual reality technology provided many benefits in sports and facilitated coaches and student-athletes [40], unfortunately no one has implemented virtual reality in Tabata training.…”
Section: Figure 1 Virtual Reality-based Tabata Trainingmentioning
confidence: 99%